Transcatheter mitral valve repair in a liver transplant candidate. Issue 12 (10th November 2022) - Ates, Ismail; Mutlu, Deniz; Inanc, Ibrahim Halil; Marmagkiolis, Konstantinos; Iliescu, Cezar A.; Kilic, Ismail Dogu; Cilingiroglu, Mehmet
Abstract: Untreated severe mitral regurgitation (MR) is associated with poor outcomes due to the adverse consequences of long‐standing volume overload on the left ventricle and left atrium, which leads to pulmonary hypertension and right‐sided heart failure. Early intervention results in favorable long‐term outcomes making appropriate timing of intervention very critical. We present a 53‐year‐old male with severe symptomatic MR and right sided‐heart failure which progressed to cardiac cirrhosis necessitating enrollment to the liver transplant list. Transcatheter mitral valve repair (TMVR) using MitraClip implantation resulted in impressive clinical improvement and resolution of cirrhosis. Eventually, the patient was taken off the transplant list. Treatment of severe MR may lead to improvements in congestive hepatopathy.